2021
DOI: 10.1093/ije/dyaa274
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking and mortality among Aboriginal and Torres Strait Islander adults in Australia

Abstract: Background Despite generally high smoking prevalences, stemming from colonization, the relationship of smoking to mortality has not been quantified reliably in an Indigenous population. We investigate smoking and mortality among Aboriginal and Torres Strait Islander adults in Australia, where current adult daily smoking prevalence is 40.2%. Methods A prospective study of 1388 cardiovascular disease- and cancer-free Aboriginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…For current smokers, residing in a TIS-funded area compared to a non-TIS-funded area was also associated with a significant 21% lower prevalence of high smoking intensity (≥21 cigarettes per day). Given that increasing smoking intensity is associated with increasing mortality risk for Aboriginal and Torres Strait Islander adults [3], the observed lower smoking intensity within TIS-funded areas is likely to reduce mortality risk for these participants. Smoking intensity is also an indicator of nicotine dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For current smokers, residing in a TIS-funded area compared to a non-TIS-funded area was also associated with a significant 21% lower prevalence of high smoking intensity (≥21 cigarettes per day). Given that increasing smoking intensity is associated with increasing mortality risk for Aboriginal and Torres Strait Islander adults [3], the observed lower smoking intensity within TIS-funded areas is likely to reduce mortality risk for these participants. Smoking intensity is also an indicator of nicotine dependence.…”
Section: Discussionmentioning
confidence: 99%
“…These systemic practices promoted, embedded and normalised widespread tobacco use within the Aboriginal and Torres Strait Islander population. As a result, smoking is the leading contributor to the burden of disease and mortality for Aboriginal and Torres Strait Islander peoples [2], with an estimated 37% of all Aboriginal and Torres Strait Islander deaths attributed to smoking [3]. The Aboriginal and Torres Strait Islander tobacco epidemic is unique due to the extended duration of high prevalence, similarity in prevalence among men and women, and distinct trends between urban, regional and remote settings [4].…”
Section: Introductionmentioning
confidence: 99%
“…The most plausible explanation is reverse causality that quitting was driven by illness or ascertainment of NPC. Therefore, we classified recent quitting as current smoking, in line with other smoking-related epidemiological studies ( 13 , 47 , 48 ). On the other hand, if the recent quitters had higher NPC risk, classifying them as current smokers would diminish the differences in NPC risk between the remaining former smokers and never smokers.…”
Section: Discussionmentioning
confidence: 99%
“…51 Further, Indigenous-specific evidence indicated that smoking causes 37% of all Aboriginal and Torres Strait Islander peoples' deaths, 50 almost twice the previous estimates. 50 Consequently, there is even greater potential to improve Indigenous health outcomes by reducing commercial tobacco use. 50 Working together as Indigenous peoples with the support of, and in collaboration with, our non-Indigenous allies, governments and non-government organisations, we have a stronger and more focused means of improving Indigenous health outcomes and countering the tobacco industry's activities.…”
Section: Special Communicationmentioning
confidence: 90%
“…50 Consequently, there is even greater potential to improve Indigenous health outcomes by reducing commercial tobacco use. 50 Working together as Indigenous peoples with the support of, and in collaboration with, our non-Indigenous allies, governments and non-government organisations, we have a stronger and more focused means of improving Indigenous health outcomes and countering the tobacco industry's activities. There are opportunities to learn from each other around the world.…”
Section: Special Communicationmentioning
confidence: 99%